Analisis Penerapan Asas Vicarious Liability dalam Peralihan Tanggung Jawab Hukum Perusahaan atas Perbuatan Pekerja - Elbert Novstyanto (Peneliti.net, 2026)
The principle of vicarious liability is a substitute liability doctrine that allows a company to be held responsible for unlawful acts committed by its employees, provided that such acts occur in the course of employment. In the context of modern corporate development, this principle has become increasingly important because companies rely on employees as the primary executors of operational activities, thereby significantly increasing the risk of harm to third parties. However, the application of vicarious liability in Indonesia continues to face various conceptual and practical challenges, particularly with regard to the limits of corporate liability, the scope of employment, and the extent of control exercised by companies over employees’ actions. The principle of vicarious liability serves as an effective legal mechanism for providing protection to victims while simultaneously encouraging companies to enhance internal supervision standards. Nevertheless, stronger regulatory frameworks and consistent jurisprudential application are still required to ensure legal certainty in corporate liability for employees’ actions.